TRACKING DOWNS CHRISTIAN DIOR IN AMERICAN POST-WWII FASHION UNTIL EARLY 1950s - Nurina Aulia Haris (Universitas Gadjah Mada, 2017)
This article studied the accomplishment of Christian Dior during his business venture in American market by using his autobiography as the main source of the research and qualitative research used as the method of study. Graves’s thought on Consumer Behavior are used as the approach of study under the umbrella of Transnational American Studies.The success of Dior in the American market is not solely because of his dresses but there are other factors that support the success of his business especially the post-World War II situation where people need something new that can make them remember the times before the war, in addition, the promotion and assessment of fashion experts through fashion and lifestyle magazines also affect people's assessment of Dior's dresses and make them affected to own his collections. Based on the theory described by Graves, people tendency to imitate others is capable to influence one's expenses and this can be seen from the phenomena occurring in American society toward Dior’s works.Concisely, the result of this research shows that the success of Dior in American market happened because of 2 things. First is the nature of human being that loves beauty, neatness, and things which make them happy. Second is the timing of his debut which was post war era where people were researching the pride they lost during the war caused by the limitation applied by the government and the condition itself therefore when Dior came with his collections they saw it as if it was their way to get back their pride as by wearing Dior’s collection it can show their social status. Keywords: Christian Dior, Fashion, Societies, World War II